If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (5x + -25) = (3x + 9) Reorder the terms: (-25 + 5x) = (3x + 9) Remove parenthesis around (-25 + 5x) -25 + 5x = (3x + 9) Reorder the terms: -25 + 5x = (9 + 3x) Remove parenthesis around (9 + 3x) -25 + 5x = 9 + 3x Solving -25 + 5x = 9 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. -25 + 5x + -3x = 9 + 3x + -3x Combine like terms: 5x + -3x = 2x -25 + 2x = 9 + 3x + -3x Combine like terms: 3x + -3x = 0 -25 + 2x = 9 + 0 -25 + 2x = 9 Add '25' to each side of the equation. -25 + 25 + 2x = 9 + 25 Combine like terms: -25 + 25 = 0 0 + 2x = 9 + 25 2x = 9 + 25 Combine like terms: 9 + 25 = 34 2x = 34 Divide each side by '2'. x = 17 Simplifying x = 17
| (5x-25)=(3x+9) | | 3k+20=5 | | -x+7-6x=19 | | 2/3=8/n | | x=9/7-30/40 | | (6+w)=6(2+w) | | 7w+4/5+12 | | -3x+y=3-4 | | 3x=-.333x+6.6666 | | 8n+7n=7n+20 | | 24/35=120/n | | 9(2Y)= | | 5x^4=135 | | 9/(x+4)^2 | | -(+3)-(-2)+(+20)-(-8)-(-11)= | | 5x-7y=18y | | -2-6x-4=3x-4-2x-1 | | 7w+4/5 | | 1/4(3x-2)=(x+10)/10 | | 4x+2+5x+6=5+3x+9 | | -31=-50.25+1.55x | | 3x-6-7x=3-2x+1 | | x-4=10x-31 | | 7x+4-2x=3x+5+9 | | 2x^2-0-15=0 | | 3d+17=2d-17 | | 12-3x=-5-3x | | -(+18)-(-2)+(+11)+(-4)-(-16)= | | 2x+10=-5x+31 | | 13=-4x+21 | | 9x+5=5+9x | | -4x+4=-7x+19 |